Application of dual stable isotopes in investigating the utilization of two wild dominant filamentous algae as food sources for Daphnia magna. Issue 1 (1st January 2017) - Fu, Hong; Xu, Jun; Xiao, Enrong; He, Feng; Xu, Peng; Zhou, Qiaohong; Wu, Zhenbin
ABSTRACT: In this study, we evaluated the effects of two dominant microfilamentous algae (i.e. Melosira granulata and Oscillatoria sp.), collected from the West Lake, on growth and metabolism of Daphnia magna . Our experiment utilized 13 C and 15 N dual labeling to calculate the carbon and nitrogen isotopic turnover rates and half-life times in D. magna. The two labeled types of filaments were offered to D. magna as sole food sources or as paired mixtures with the unlabeled Scenedesmus obliquus. Labeled S. obliquus served as the control. Combined results showed that D. magna had a higher grazing rate on Oscillatoria sp. than on M. granulate and a small percentage of unlabeled S. obliquus addition could improve the grazing rate in both filamentous algae, especially for Oscillatoria sp., which had the highest carbon and nitrogen isotopic turnover rates and the lowest half times, even superior to the sole S. obliquus treatment. Our study revealed that D . magna could utilize the two dominant filamentous algae as a food source for their growth and metabolism, and a small percentage addition of S. obliquus could ameliorate the negative impact of these two filamentous algae on D. magna .